Multiscale mechanics of tissue‐engineered cartilage grown from human chondrocytes and human‐induced pluripotent stem cells. Issue 9 (20th March 2020) - Middendorf, Jill M.; Diamantides, Nicole; Shortkroff, Sonya; Dugopolski, Caroline; Kennedy, Stephen; Cohen, Itai; Bonassar, Lawrence J.
Abstract: Tissue‐engineered cartilage has shown promising results in the repair of focal cartilage defects. However, current clinical techniques rely on an extra surgical procedure to biopsy healthy cartilage to obtain human chondrocytes. Alternatively, induced pluripotent stem cells (iPSCs) have the ability to differentiate into chondrocytes and produce cartilaginous matrix without the need to biopsy healthy cartilage. However, the mechanical properties of tissue‐engineered cartilage with iPSCs are unknown and might be critical to long‐term tissue function and health. This study used confined compression, cartilage on glass tribology, and shear testing on a confocal microscope to assess the macroscale and microscale mechanical properties of two constructs seeded with either chondrocyte‐derived iPSCs (Ch‐iPSCs) or native human chondrocytes. Macroscale properties of Ch‐iPSC constructs provided similar or better mechanical properties than chondrocyte constructs. Under compression, Ch‐iPSC constructs had an aggregate modulus that was two times larger than chondrocyte constructs and was closer to native tissue. No differences in the shear modulus and friction coefficients were observed between Ch‐iPSC and chondrocyte constructs. On the microscale, Ch‐iPSC and chondrocyte constructs had different depth‐dependent mechanical properties, neither of which matches native tissue. These observed depth‐dependent differences may be important to the function of the implant. Overall, this comparison of multiple mechanical properties of Ch‐iPSC and chondrocyte constructs shows that using Ch‐iPSCs can produce equivalent or better global mechanical properties to chondrocytes. Therefore, iPSC‐seeded cartilage constructs could be a promising solution to repair focal cartilage defects. The chondrocyte constructs used in this study have been implanted into humans for clinical trials. Therefore, Ch‐iPSC constructs could also be used clinically in place of the current chondrocyte construct.